Transformation of Modern Culinary Entrepreneurs: Strategies and Challenges in the Face of the Modern Era - Agus Yulistiyono; Eva Andriani; Arief Yanto Rukmana (Westscience Press, 2023)
This research delves into the transformation of modern culinary entrepreneurs in West Java, Indonesia, investigating the strategies they employ and the challenges they face in adapting to the demands of the modern era. Through a mixed-methods approach encompassing surveys, interviews, and case studies, the study uncovers how these entrepreneurs navigate the delicate balance between tradition and innovation. he findings offer profound insights into the dynamic interplay between cultural heritage and contemporary demands, providing actionable recommendations for both entrepreneurs and policymakers. This research contributes to the broader discourse on culinary entrepreneurship by unveiling the tapestry woven by these entrepreneurs as they redefine tradition, embrace change, and shape the culinary narrative of West Java in the modern era.